Rocks and clay: Potters' technological choices within the cultural dynamics of Bronze Age Kazakhstan. - Paula N Doumani Dupuy; Silvia Amicone; Marcel Frenken; Jack Berner; Taylor Hermes; Michael D Frachetti; Galymzhan Kiyasbek (PLoS ONE)
Through regular interactions with their neighbors, diverse groups inhabiting areas along the Inner Asian Mountain Corridor during the Bronze Age formed dynamic interregional networks that saw the proliferation and persistence of shared material cultures over vast geographic areas. In this paper we advocate for ceramics analyses that combine both macro- and micro-scale technological studies alongside those of style, in order not to lose sight of the actual people who drove defining transformations in the Bronze Age. We present a petrographic study of pottery from the Zhetysu region, southeastern Kazakhstan, to examine diachronic technological traditions with a special focus on routines of selection and raw material processing. Our results demonstrate site-specific potting technologies as well as traits that transcend both time and space across episodes of high genetic turnover in the human population.